2019
DOI: 10.1139/bcb-2018-0196
|View full text |Cite
|
Sign up to set email alerts
|

On the oxidative damage by cadmium to kidney mitochondrial functions

Abstract: In the kidney, the accumulation of heavy metals such as Cd2+ produces mitochondrial dysfunctions, i.e., uncoupling of the oxidative phosphorylation, inhibition of the electron transport through the respiratory chain, and collapse of the transmembrane electrical gradient. This derangement may be due to the fact that Cd2+ induces the transition of membrane permeability from selective to nonselective via the opening of a transmembrane pore. In fact, Cd2+ produces this injury through the stimulation of oxygen-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A previous animal study also found that subchronic low-dose Cd exposure may cause renal injury, including decreased renal function, destruction of the renal structure, and inflammation, in a dose-dependent manner . The mechanism of Cd-induced kidney injury is relatively clear, including oxidative stress, DNA damage, inflammation, mitochondrial dysfunction, apoptosis, and autophagy. , In addition, it has been proposed that Cd exposure can eliminate reserves of kidney function, which may increase an individual’s susceptibility to other risk factors of kidney failure …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous animal study also found that subchronic low-dose Cd exposure may cause renal injury, including decreased renal function, destruction of the renal structure, and inflammation, in a dose-dependent manner . The mechanism of Cd-induced kidney injury is relatively clear, including oxidative stress, DNA damage, inflammation, mitochondrial dysfunction, apoptosis, and autophagy. , In addition, it has been proposed that Cd exposure can eliminate reserves of kidney function, which may increase an individual’s susceptibility to other risk factors of kidney failure …”
Section: Discussionmentioning
confidence: 99%
“…37 The mechanism of Cd-induced kidney injury is relatively clear, including oxidative stress, DNA damage, inflammation, mitochondrial dysfunction, apoptosis, and autophagy. 38,39 In addition, it has been proposed that Cd exposure can eliminate reserves of kidney function, which may increase an individual's susceptibility to other risk factors of kidney failure. 33 MC-LR and Cd coexist widely in the aquatic ecosystem with the aggravation of environmental pollution and the continuous discharge of industrial, agricultural, and domestic sewage.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium can enter mitochondria and accumulate therein [ 113 , 114 ]. This is likely facilitated by mitochondrial membrane channels, and solute molecule carriers and receptors [ 114 ].…”
Section: Effects Of Cadmium On Mitochondrial Functionmentioning
confidence: 99%
“…While mitochondria are the primary sites of ROS generation, excessive ROS accumulation can impair mitochondrial membrane potential, leading to irreversible oxidative damage and cell death ( Huang et al, 2019 ; Murphy et al, 2016 ; Orrenius et al, 2007 ; Wang et al, 2020 ). However, a reduction in membrane potential can also lead to the recruitment of mitochondrial receptors, which can combine with autophagy adapters and LC3 to activate mitophagy ( Pavón et al, 2019 ). Although most studies on the regulatory mechanisms of mitophagy have focused on the PINK1-PRKN pathway, emerging evidence suggests that this pathway is not the sole mechanism, and mitophagy can still occur in the absence of parkin ( Villa et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%